Susceptibility of Stenotrophomonas maltophilia clinical strains in China to antimicrobial combinations. (October 2014) - Hu, Li-Fen; Gao, Li-Ping; Ye, Ying; Chen, Xi; Zhou, Xiang-Tian; Yang, Hai-Fei; Liiu, Yan-Yan; Mei, Qing; Li, Jia-Bin
<x content-type="archive" xml:space="preserve">Abstract</x> We aimed to investigate the activity levels of several combinations of antimicrobials against Stenotrophomonas maltophilia. In this study, the antimicrobial susceptibility of S. maltophilia clinical isolates was determined, and the synergistic activity of three pairs of antimicrobial combinations was evaluated by the fractional inhibitory concentration index (FICI). The antimicrobial susceptibility in vitro against 83 S. maltophilia strains was greater for minocycline (80·7%) than for trimethoprim–sulfamethoxazole (51·8%), and levofloxacin (50·6%). The rate of resistance was highest for ticarcillin–clavulanate and ceftazidime (63·8%) and resistance to trimethoprim–sulfamethoxazole (TMP–SMX) was 48·2%. All three combinations were tested against susceptible isolates. Two of the combinations, TMP–SMX+ceftazidime and levofloxacin+ceftazidime were more effective than the combination of TMP–SMX+levofloxacin. We recommend acquiring more clinical data in order to explore combination therapy, which is a promising treatment of S. maltophilia infections.